The Paradox of Fintech and Gen Z Consumption in Sustainable Development: Implications for Community Development Planning in Gorontalo Province - Kalzum R. Jumiyanti; Barmin R Yusuf; Mohamad Afan Suyanto (Fakultas Ekonomi dan Bisnis Universitas Lampung, 2026)
Fintech transformation in Gorontalo accelerates Gen Z transactions, but raises a paradox between ease of consumption and sustainability demands; This study aims to map strengths, weaknesses, opportunities, threats and formulate WT interventions for community development planning. Exploratory qualitative research involved 67 Gen Z students (18–27 years old) who are financially autonomous and regular users of e-wallets, paylater, or digital investments; Data were collected through focus group discussions and semi-structured face-to-face interviews and analyzed with SWOT thematization. The results show that the main strengths of fintech are understood to be transaction efficiency and withdrawal monitoring, while the dominant weaknesses are frictionless spending, promotional impulsivity, and the illusion of paylater's affordability. Interpretation shows that self-control is strengthened when the monitoring feature is consciously activated. Gen Z considers the biggest opportunities to be in budget control features, microlearning, and impact feedback, but feel the threat in the form of consumptive debt, FOMO, e-commerce overconsumption, and consumer protection risks. Research emphasizes that fintech can be a behavioral infrastructure for sustainable development if supported by choice design (limits, transaction breaks, notifications) and literacy-protection governance; Further studies are suggested to test the effectiveness of WT packages on regional programs and measure changes in consumption behavior over time.